2020
DOI: 10.1038/s41467-020-15313-w
|View full text |Cite
|
Sign up to set email alerts
|

The ribosome-associated complex RAC serves in a relay that directs nascent chains to Ssb

Abstract: The conserved ribosome-associated complex (RAC) consisting of Zuo1 (Hsp40) and Ssz1 (non-canonical Hsp70) acts together with the ribosome-bound Hsp70 chaperone Ssb in de novo protein folding at the ribosomal tunnel exit. Current models suggest that the function of Ssz1 is confined to the support of Zuo1, however, it is not known whether RAC by itself serves as a chaperone for nascent chains. Here we show that, via its rudimentary substrate binding domain (SBD), Ssz1 directly binds to emerging nascent chains pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 59 publications
4
41
0
Order By: Relevance
“…The supernatant was loaded onto a Superdex-G25 gel filtration column equilibrated with gel filtration buffer (20 mM Hepes/KOH pH 7.4, 100 mM KOAc, 2 mM MgOAc 2 , 2 mM DTT, 0.5 mM PMSF, 20% glycerol) at a flow rate of 1.5 ml min −1 . Peak fractions with the highest A 260 were pooled, were supplemented with 1 mM CaCl 2 , were treated with 300 U ml −1 micrococcal nuclease (Roche) for 15 min at 20 °C followed by addition of 2 mM EGTA, and aliquots of the resulting yeast translation extract, were stored at −80 °C 74 , 75 . RNCs were generated via translation reactions primed with the stop codon-less transcripts at 20 °C for 80 min 42 , 74 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant was loaded onto a Superdex-G25 gel filtration column equilibrated with gel filtration buffer (20 mM Hepes/KOH pH 7.4, 100 mM KOAc, 2 mM MgOAc 2 , 2 mM DTT, 0.5 mM PMSF, 20% glycerol) at a flow rate of 1.5 ml min −1 . Peak fractions with the highest A 260 were pooled, were supplemented with 1 mM CaCl 2 , were treated with 300 U ml −1 micrococcal nuclease (Roche) for 15 min at 20 °C followed by addition of 2 mM EGTA, and aliquots of the resulting yeast translation extract, were stored at −80 °C 74 , 75 . RNCs were generated via translation reactions primed with the stop codon-less transcripts at 20 °C for 80 min 42 , 74 .…”
Section: Methodsmentioning
confidence: 99%
“…Models of ribosomal particles were generated with PyMOL 2.2.0. Polyclonal antibodies directed against Srp54 42 (1:4000), Sgt2 24 (1:5000), Get4 24 (1:5000), Get5 24 (1:5000), Get3 24 (1:5000), Rpl4 24 (1:10,000), Rpl24 42 (1:10,000), Rpl35 60 (1:10,000), Rpl31 60 (1:5000), Rpl26 60 (1:2000), Rps9 42 (1:5000), Pgk1 75 (1:2000), Kar2 76 (1:2000), Sse1 42 (1:20,000) (Eurogentec, Rospert lab antibody collection), and PAP (Sigma ID P1291, 1:5000) were raised in rabbit. α-FLAG (Sigma F3165, 1:2000) and α-His (Qiagen 34660, 1:2000) are monoclonal antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Here we found that RAC deletions lead to the generation of substantially different prion variants than ssb1/2Δ strains. Most recently, RAC was found to bind to translating nascent peptide chains at the ribosomal tunnel exit like ribosomal Ssb1/2p (76). Ribosomeassociated Zuo1p, Ssz1p, and Ssb1/2p sequentially contact growing nascent chains of minimum length 40, 45, and 50 residues, respectively, and hand over chains to the next chaperone in a relay for cotranslational de novo protein folding.…”
Section: What Controls Generation and Curing Of [Psi+sbs] Vs [Psi+szs] Ormentioning
confidence: 99%
“…As with folding in the cell, the involvement of other factors must not be overlooked. A wide array of ribosome-associated chaperones are vital for nascent chain homeostasis 4,5,[81][82][83] and the degree to which they choreograph assembly steps is yet to be elucidated. Furthermore, because interface size alone does not fully explain the range of affinities observed in a growing number of complexes [46][47][48][49] , it will be exciting to see whether binding affinity plays a role in colocalising mRNA molecules in eukaryotic cells 13,14,19,21,84,85 .…”
Section: Discussionmentioning
confidence: 99%